Agreement between schoolchildren and their parents on rating the child's oral health-related quality of life - Thays Torres do Vale OLIVEIRA; Aryane Marques MENEGAZ; Mateus Andrade ROCHA; Vanessa Polina Pereira COSTA; Taís de Souza BARBOSA; Marília Leão GOETTEMS; Marina Sousa AZEVEDO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The perceptions of parents/caregivers regarding their children's oral health can influence the standard of care and decision-making regarding oral health. The children's perspective on their own oral health-related quality of life (OHRQoL) may differ from the parents/caregivers' views. This cross-sectional study aimed to analyze the agreement between the perceptions of parents/caregivers and schoolchildren regarding OHRQoL. It was conducted with a sample of children between 8 and 11 years old and their parents/caregivers from Pelotas. Children answered the Child Perceptions Questionnaire 8-10 (CPQ), and parents/caregivers answered the short form of the Parental-Caregiver Perceptions Questionnaire (P-CPQ). Socioeconomic data were also collected. Children's dental caries, traumatic dental injuries, and malocclusions were examined. The Spearman's correlation test was performed. A total of 119 parents/caregivers-children pairs were included. There was an agreement between the total scores of parents/caregivers and children (0.2770; p = 0.003), in the oral symptoms (0.1907; p = 0.038), and functional limitations (0.2233; p=0.015) domains. The Bland-Altman graph showed an agreement between children's and parents/caregivers' OHRQoL total score, but there was an underestimation of approximately two points in the parents/caregivers' perception compared to the children's score. There was an agreement between the reports of parents/caregivers and children regarding children's OHRQoL.